2018
DOI: 10.1177/0022034518809086
|View full text |Cite
|
Sign up to set email alerts
|

A Chemical Approach to Optimizing Bioactive Glass Dental Composites

Abstract: The chemical microenvironment surrounding dental composites plays a crucial role in controlling the bacteria grown on these specialized surfaces. In this study, we report a scanning electrochemical microscopy (SECM)-based analytic technique to design and optimize metal ion-releasing bioactive glass (BAG) composites, which showed a significant reduction in biofilm growth. SECM allows positioning of the probe without touching the substrate while mapping the chemical parameters in 3-dimensional space above the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 32 publications
3
24
0
Order By: Relevance
“…Quorum quenching enzymes [110], adhesin repressors [111], nanoparticle-based copolymers [56,112] and metal-chelator approaches [113,114] have been studied so far to prevent biofilm formation or to eradicate biofilms. To date, only a few studies concerning antimicrobial effects have been published using SECM [82,112,115,116]. Silver nanoparticles (AgNPs) and Ag(I) at low concentrations are known as a very powerful antimicrobial agent, which, to date, are used in many consumer products and clinical applications [117].…”
Section: Antibacterial Agentsmentioning
confidence: 99%
“…Quorum quenching enzymes [110], adhesin repressors [111], nanoparticle-based copolymers [56,112] and metal-chelator approaches [113,114] have been studied so far to prevent biofilm formation or to eradicate biofilms. To date, only a few studies concerning antimicrobial effects have been published using SECM [82,112,115,116]. Silver nanoparticles (AgNPs) and Ag(I) at low concentrations are known as a very powerful antimicrobial agent, which, to date, are used in many consumer products and clinical applications [117].…”
Section: Antibacterial Agentsmentioning
confidence: 99%
“…Centuries ago, various metals, such as silver, gold, and zinc, were used as bactericidal and bacteriostatic agents . Today, to address the aforementioned problems, antibacterial composites and adhesive systems have been developed, with various approaches used to confer antibacterial activity . In terms of resin‐based dental composites, one approach is to include antibacterial agents, such as fluoride and chlorhexidine, in the resin matrix.…”
Section: Introductionmentioning
confidence: 99%
“…These include stimulating bone formation, desensitizing teeth, remineralizing white spot lesions, and restoring teeth. A recent study reported that the release of metal ions by BAG impeded the formation of oral biofilms . The authors of the study recommended that BAG should be added to composites.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations